Clonal genomic population structure of Beauveria brongniartii and Beauveria pseudobassiana : Pathogens of the common European cockchafer ( Melolontha melolontha L.) - Chiara Pedrazzini; Stephen A. Rehner; Hermann Strasser; Niklaus Zemp; Rolf Holderegger; Franco Widmer; Jürg Enkerli (Environmental Microbiology, 2024)
Beauveria brongniartii is a fungal pathogen that infects the beetle Melolontha melolontha , a significant agricultural pest in Europe. While research has primarily focused on the use of B. brongniartii for controlling M. melolontha , the genomic structure of the B. brongniartii population remains unknown. This includes whether its structure is influenced by its interaction with M. melolontha , the timing of beetle‐swarming flights, geographical factors, or reproductive mode. To address this, we analysed genome‐wide SNPs to infer the population genomics of Beauveria spp., which were isolated from infected M. melolontha adults in an Alpine region. Surprisingly, only one‐third of the isolates were identified as B. brongniartii , while two‐thirds were distributed among cryptic taxa within B. pseudobassiana , a fungal species not previously recognized as a pathogen of M. melolontha . Given the prevalence of B. pseudobassiana , we conducted analyses on both species. We found no spatial or temporal genomic patterns within either species and no correlation with the population structure of M. melolontha , suggesting that the dispersal of the fungi is independent of the beetle. Both species exhibited clonal population structures, with B. brongniartii fixed for one mating type and B. pseudobassiana displaying both mating types. This implies that factors other than mating compatibility limit sexual reproduction. We conclude that the population genomic structure of Beauveria spp. is primarily influenced by predominant asexual reproduction and dispersal.